Turkish-Islamic Ceramics of The Nigde/Tyana (Kemerhisar) Excavations - Yunus Emre Karasu (Sanat Tarihi Yıllığı)
The ancient city of Tyana, located in Kemerhisar town of Bor district of Niğde province, It is one of the most important settlements of the Middle Ages. After the Battle of Manzikert in 1071, Turkish and Islamic culture began to spread in Anatolia. In the 13th century, the Seljuks dominated the Niğde region, where Tyana was also located. Although the region lost its importance due to political turmoil for a while during the Danişmets period, its brightest time was during the Anatolian Seljuks period. The activities of the Seljuks in the region and its location near the trade routes contributed greatly to its development in this period. Ceramics that provide important information about daily life, socio-economic structure and trade are also frequently encountered in the Tyana excavation. This study will examine the medieval ceramics found in the excavations in the Tyana region, a large number of which were made with monochromatic glaze, sgraffito, champleve, painted sgraffito and underglaze painting techniques. The ceramics, extensively examined according to their paste, form, and decoration and composition characteristics, provide important information about the settlement in the region during and after the Anatolian Seljuk period. The similarity of the ceramics dated between the 13th and 15th centuries, especially with Komana, which is one of the layered excavations in Anatolia, is very important. Determining the ceramic production in the Anatolian Seljuk period and the following periods will contribute significantly to the understanding of the socio-economic structures in these period.